Benign epileptiform discharges of childhood and associated conditions - K. Yu. Mukhin (Русский журнал детской неврологии)
This article provides a detailed description of benign epileptiform discharges of childhood (BEDC) as one of electroencephalography patterns in children. We emphasize that BEDC are not specific for both idiopathic (genetic) focal epilepsy and epilepsy in general. BEDC can be observed in a number of various disorders and also in neurologically healthy children. We developed a detailed classification of BEDC-associated states that are divided into 3 groups: neurologically healthy children, children with various forms of epilepsy, and patients with various neurological disorders without epilepsy. We found that there are 2 main factors responsible for BEDC in electroencephalogram: genetic predisposition and white matter lesions, usually occurring during the antenatal or perinatal period. BEDC should be considered rather a manifestation of congenital abnormalities in brain maturation than a marker of epilepsy. We also discuss the need for therapy in patients with BEDC-associated states.